The birth of critical thinking in Republican Rome - Moatti, Claudia 1954- (Cambridge University Press, 2015)
"In this classic work, now appearing in English for the first time, Claudia Moatti analyses the intellectual transformation that occurred at the end of the Roman Republic in response both to the political crisis and to the city's expansion across the Mediterranean. This was a period of great cultural dynamism and creativity when Roman intellectuals, most notably Cicero and Varro, began to explore all areas of life and knowledge and to apply critical thinking to the reassessment of tradition and the development of a systematic new understanding of the Roman past and present. This movement, linked to the development of writing, challenged old forms of authority and adhesion, belief and behaviour, without destroying tradition; and for this reason this rational trend can be described not as a cultural but as an epistemological revolution whose greatest achievement, Professor Moatti argues, was the development of the system of Roman law"..